PENGARUH COMPANY REPUTATION, E-SOCIAL INFLUENCE DAN E-TRUST TERHADAP KEPUTUSAN BERDONASI DI APLIKASI DOMPET DHUAFA - Ristia Tri Ananda; Femei Purnamasari; Yulistia Devi (POLITEKNIK LP3I JAKARTA, 2025)
In this era of globalization, the internet has become a daily necessity, with all activities related to smartphones and the internet. This research aims to examine the influence of company reputation, e-social influence, and e-trust on donation decisions in the dhuafa wallet application, focusing on Gen Z in Bandar Lampung City. This study aims to determine how these factors affect donation decisions. The theory used in this research is the Technology Acceptance Model (TAM). The method employed is a quantitative descriptive approach, with a sample size of 100 Gen Z individuals in Bandar Lampung City, calculated using the Slovin formula. Data collection was carried out through questionnaires, and data processing was performed using SmartPLS 4. Based on the research results, it can be concluded that company reputation does not affect donation decisions, while e-social influence and e-trust have a significant impact on donation decisions.